Persepsi Mahasiswa Pendidikan IPS Terhadap Pendidikan Multikultural - Padang, Ariani Tandi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The State of Indonesia is pinned as a multicultural country. This pinning is of course based on the fact that Indonesia consists of 1,340 ethnic groups in the country. Of course, this diversity should be a wealth in itself for Indonesia, but not infrequently this diversity actually triggers conflicts between ethnic groups, religions and races. Therefore, this study wants to know the perceptions of social studies education teacher students towards multicultural education. The research subjects used were 16 social studies teacher students at a private university, Tangerang. They come from several tribes and races of Indonesia. The research method used is qualitative. The results of the study showed that 68.75% of students were able to define multicultural education up to the application stage. 100% of students consider multicultural education important to do. 56% of students agree that education can be used as a means of planting multicultural education. This is also in line with their experience of wanting to interact with people of different ethnicities, religions and races because they are influenced by the role of the teacher (63%) and family values (75%).